Dietary Compensatory Feeding in Manduca sexta (Lepidoptera: Sphingidae) Larvae - Intan Ahmad (Jurnal Perlindungan Tanaman Indonesia, 2001)
The aim of the experiments reported in this article is to gain further insight into the nature and control of dietary compensatory feeding: i.e., to investigate whether one or another nutrient is more important in eliciting compensatory behavior. The response of 4th-instar Manduca sexta to dilution of either protein or carbohydrate nutrient in the diet was measured. In these experiments, ratio of protein and carbohydrate selected, food consumption and utilization parameters were measured. Fourth instars were given the opportunity to self-select between two defined diets, one which differed between treatments in protein content and a complementary diet, which contained the standard amount of carbohydrate and did not vary from treatment to treatment. In response to protein dilution, the larvae compensated by consuming more of both the protein-containing and carbohydrate containing diets. In most of the cases, this compensation was sufficient to maintain normal growth, although AD, ECI, and ECD declined with the reduction of protein in the protein-containing diet. When larvae self-selected from a standard protein diet that was paired with a carbohydrate diet with one of six concentrations of sucrose, they responded by eating more from the protein-containing diet as the sucrose content of the carbohydrate diet declined. The growth and efficiency of food use was little affected over the entire range of carbohydrate diets tested.Although apparently the regulation of carbohydrate intake is not as strong as the regulation of protein intake, it seems that in response to dilution, the larvae select at each concentration a protein:carbohydrate ratio that is favorable to them.